2014
DOI: 10.1097/ncc.0000000000000159
|View full text |Cite
|
Sign up to set email alerts
|

A Tailored Web-Based Psychoeducational Intervention for Cancer Patients and Their Family Caregivers

Abstract: Background Most programs addressing psychosocial concerns of cancer survivors are in-person programs that are expensive to deliver, have limited availability, and seldom deal with caregivers’ concerns. Objective This study examined the feasibility of translating an efficacious nurse-delivered program (FOCUS Program) for patients and their caregivers to a tailored, dyadic web-based format. Specific aims were to: (i) test the preliminary effects of the web-based intervention on patient and caregiver outcomes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
193
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 134 publications
(204 citation statements)
references
References 30 publications
8
193
2
1
Order By: Relevance
“…Five studies reported significant differences in Quality of Life aspects: three of them showed significant effects in all dimensions of Quality of Life [52,65,67]; Two studies showed significant effects in spiritual and social well-being [59,65], while one study [60] showed significant outcomes in social well-being. Emotional distress or stress symptoms revealed significant differences between pre-and post-treatment in five of the considered studies [50,52,65,67,69], while both depressive symptoms [55,57,65] and perceived social support [62,65,66] improved in three different trials. Furthermore, included articles reported significant effects -albeit smaller -in other measured outcomes: after the completion of the interventions, family members also experienced less anxiety, less sense of disruptiveness, hopelessness and uncertainty, less burden, and negative appraisal of caregiving.…”
Section: Measured Outcomesmentioning
confidence: 99%
See 4 more Smart Citations
“…Five studies reported significant differences in Quality of Life aspects: three of them showed significant effects in all dimensions of Quality of Life [52,65,67]; Two studies showed significant effects in spiritual and social well-being [59,65], while one study [60] showed significant outcomes in social well-being. Emotional distress or stress symptoms revealed significant differences between pre-and post-treatment in five of the considered studies [50,52,65,67,69], while both depressive symptoms [55,57,65] and perceived social support [62,65,66] improved in three different trials. Furthermore, included articles reported significant effects -albeit smaller -in other measured outcomes: after the completion of the interventions, family members also experienced less anxiety, less sense of disruptiveness, hopelessness and uncertainty, less burden, and negative appraisal of caregiving.…”
Section: Measured Outcomesmentioning
confidence: 99%
“…These improved outcomes were: caregiver self-efficacy, Quality of Life, distress, depression, appraisal of caregiving, and perceived social support. Caregiver self-efficacy both in managing own emotions and in helping the patients to control symptoms was measured in five studies [52,59,61,67,70] and was always statistically significant. Five studies reported significant differences in Quality of Life aspects: three of them showed significant effects in all dimensions of Quality of Life [52,65,67]; Two studies showed significant effects in spiritual and social well-being [59,65], while one study [60] showed significant outcomes in social well-being.…”
Section: Measured Outcomesmentioning
confidence: 99%
See 3 more Smart Citations